Tradisi Selamatan Kematian Nyatus Nyewu: Implikasi Nilai Pluralisme Islam Jawa - Hendrajaya, Jerry; Almu’tasim, Amru (Jurnal Lektur Keagamaan, 2019)
The meaning of tradition in this theme is more directed at the chronology of ritual salvation for Nyatus Nyewu. Javanese people interpret salvation as a media to offer prayers for the salvation of those who died and those left behind. Implications of the meaning of the perspective of Islamic education contained in Nyatus Nyewu and Nyewu salvation include; the moral values of people die, the value of faith, the value of almsgiving, the value of ukhuwah Islamiyah and solidarity and value please help. The impact of the value of Islamic education contained in the tradition of Nyatus Nyewu on the behavior of religion, does not occur immediately comprehensively in Javanese society but rather affects certain groups who have a strong spirit and awareness of religion.Keywords: Javanese Tradition, Selamatan, Nyatus Nyewu Makna tradisi dalam tema ini lebih mengarah pada kronologisasi ritual selamatan Nyatus Nyewu. Masyarakat Jawa memaknai selamatan sebagai sebuah media untuk memanjatkan doa memohon keselamatan bagi yang meninggal dan yang ditinggal. Implikasi makna perspektif pendidikan Islam yang terkandung dalam selamatan Nyatus Nyewu dan nyewu antara lain; nilai akhlak terhadap orang meninggal dunia, nilai keimanan, nilai sedekah, nilai ukhuwah Islamiyah dan solidaritas serta nilai tolong menolong. Dampak nilai pendidikan Islam yang terkandung dalam tradisi Nyatus Nyewu nyewuterhadap tingkah laku keagamaan, tidak terjadi serta-merta komprehensif pada masyarakat Jawa melainkan berpengaruh pada kalangan tertentu yang memiliki jiwa dan kesadaran akan keagamaan yang kuat.Kata Kunci : Tradisi Jawa, Selamatan, Nyatus Nyewu